Clinical diagnostic accuracy of the HIV rapid test ACCU-TELL anti-HIV 1 + 2 in sub-Saharan African region - Veronique M´pirah; Steeve Mbomo; Armel Mintsa; Amel Alame Emane; Ngondziga Ongala Djeff Chirack; Ndong Mebaley Telstar Ghestin; Quenard Edwina Lorine; Saidou Mahmoudou; Joel Fleury Djoba Siawaya; Paulin N. Essone (BMC Infectious Diseases)
Abstract Human Immunodeficiency Virus (HIV) is still a major health challenge. Around 1.5 million people are newly infected with HIV in the world every year. Screening and identification of HIV infected individuals is a major health challenge in the management of this pandemic. The last decades have seen the development and deployment of HIV Rapid Diagnostic Tests (RDTs). These tests present numerous advantages in the management of HIV and are suitable in resource-limited settings. Unfortunately, many RDTs are deployed in low and middle income countries without primary evaluation in this setting. The current work evaluated the accuracy of Accu-Tell HIV rapid test in Sub-Saharan setting. We have performed a cross-sectional prospective study and included all patients visiting the national laboratory of public health in Libreville, Gabon, for a period of three months. We have selected RecombiLISA HIV1 + 2 Ab ELISA as gold standard. We have also included Determine HIV-1/2 Ag/Ab Combo as a control validated and recommended rapid test. Seven hundred forty-four participants visited our laboratory for HIV testing during the three-months study period with a mean age of 34 (SD: 14%) years old. ELISA and rapid tests (Determine and Accu-Tell) were performed on all study participants. 57, 61 and 62 participants were found positive for Accu-Tell, Determine and ELISA, respectively. For a sensitivity and specificity of 93% and 99%, respectively, Accu-Tell registered four (04) false positive and nine (09) false negative results. We observed six (06) false positive and seven (07) false negative results with Determine for a sensitivity and specificity of 90 and 99%, respectively. Accu-Tell and Determine have similar accuracy in detecting HIV infection in our setting. We have unfortunately observed a strong cross reaction between HIV1 and HIV2 with Accu-Tell. This test may not be used to differentiate HIV1 and HIV2.